Formula Optimization From Halal Lip Cream Variety With Tomato Extract (Lycopersicum esculentum L.) - Ginanjar Putri Nastiti; Abdul Qosim; Nabilla Puspitaningrum; M. Nauval Nadhirul Fuadi (Journal of Islamic Pharmacy, 2023)
The majority of the population of Indonesia embraces Islam, which is obliged to consume halal products. One of the most popular products is the lip cream variant. One of the forms and physical stability of halal lip cream variants is influenced by the selection and content of the base Wax. The halal aspect of the lip cream variant is viewed from the components and processing process. Tomatoes are used as natural dyes with a concentration of 5% to support the halal element. This research aims to get the optimal Wax base in the halal lip cream formula so that the variant can meet the necessities. This research was conducted experimentally by using a base comparison. The base Wax used in this research were Carnauba Wax (15%), Microcrystalline Wax (15%), and a combination of the two (6%:9%). The results showed an orange color variant, semi-solid form, rose smell, homogeneous composition, pH, spreadability, good smearing power, and not irritating. The adhesion test showed that F1 adhered well while F2 and F3 did not. In the stability test, F1 and F3 were stable, while F2 was unstable with the formation of 2 phases. Based on the evaluation of the halal lip cream variant showed the most optimal result, namely the F1 combination of Carnauba Wax and Microcrystalline Wax